A Risk Aversion under Fuzzy Set and System Environment - Shubanath, (Enhanced Knowledge in Sciences and Technology, 2022)
Risk aversion play an important role in economics, finance, psychology and especially decision making. This research conduct a study using random data by proving Arrow-Pratt measures using Jensen-type operators. The methodology is based on the objectives. The methodology includes formulating utility functions under decision making, triangular and trapezoidal fuzzy number is introduced to reduce the complexity of determining the utility function of a decision maker, provingPratt’s theorem for possibilistic risk aversion associated with fuzzy number, a utility function and weighting function under Jensen type operators and also risk premium was set defining as a measure of risk aversion discovered and explain using the possibilistic expected value using Arrow-Pratt formula The results and discussion yields all the three objectives based on the methodology done in the previous section. The main notions are the possibilistic risk premium and the possibilistic relative risk premium associated with a fuzzy number and a utility function using Arrow-Pratt theorems with Jensen type operators under risk aversion.